One Way Traffic: Base‐to‐Backbone Hole Transfer in Nucleoside Phosphorodithioate. Issue 43 (9th June 2020) - Kaczmarek, Renata; Ward, Samuel; Debnath, Dipra; Jacobs, Taisiya; Stark, Alexander D.; Korczyński, Dariusz; Kumar, Anil; Sevilla, Michael D.; Denisov, Sergey A.; Shcherbakov, Viacheslav; Pernot, Pascal; Mostafavi, Mehran; et al.
Abstract: The directionality of the hole‐transfer processes between DNA backbone and base was investigated by using phosphorodithioate [P(S − )=S] components. ESR spectroscopy in homogeneous frozen aqueous solutions and pulse radiolysis in aqueous solution at ambient temperature confirmed initial formation of G .+ ‐P(S − )=S. The ionization potential of G‐P(S − )=S was calculated to be slightly lower than that of guanine in 5′‐dGMP. Subsequent thermally activated hole transfer from G .+ to P(S − )=S led to dithiyl radical (P‐2S . ) formation on the μs timescale. In parallel, ESR spectroscopy, pulse radiolysis, and density functional theory (DFT) calculations confirmed P‐2S . formation in an abasic phosphorodithioate model compound. ESR investigations at low temperatures and higher G‐P(S − )=S concentrations showed a bimolecular conversion of P‐2S . to the σ 2 ‐σ* 1 ‐bonded dimer anion radical [‐P‐2S - . 2S‐P‐] − [Δ G (150 K, DFT)=−7.2 kcal mol −1 ]. However, [‐P‐2S - . 2S‐P‐] − formation was not observed by pulse radiolysis [Δ G ° (298 K, DFT)=−1.4 kcal mol −1 ]. Neither P‐2S . nor [‐P‐2S - . 2S‐P‐] − oxidized guanine base; only base‐to‐backbone hole transfer occurs in phosphorodithioate. Abstract : Tracking holes : The nature and directionality of the hole‐transfer pathways in phosphorodithioate systems and identification of the radicals involved was achieved by employing a unique combination of synthesis, ESR spectroscopic studies in frozen aqueous solution at low temperature, pulse radiolysis in aqueous solution at room temperature, and ab initio DFT calculations.